Optic Disc Cupping - Kamila Nastiti; Putu Ristyaning Ayu Sangging; Rani Himayani (CV. Jasa Sukses Abadi, 2023)
Optic disc cupping is an enlargement of the cup and disc diameter ratio which is known as one of the characteristics of glaucoma. Glaucoma itself is one of the leading causes of blindness in Indonesia. Diabetes, heart disease, hypertension, nearsightedness and farsightedness can be risk factors for optic disc cupping due to glaucoma. Optic disc cupping can also be caused by various cases of non-glaucoma optic neuropathy. Distinguishing glaucomatous and non-glaucoma-induced optic disc cupping is a challenge for the observer. This research was conducted using the literature study method by conducting literature searches from various international and national journal sources. This study aims to collect data that is relevant to the material that is interested in being studied, namely regarding optical disc cupping. The results of the research that has been done are in the form of deepening material regarding optic disc cupping. The results showed that while the ratio of the cup to the optic nerve disc is quite variable in humans, the contours of the cup should be determined by biomicroscopic background assessment in order not to rely solely on color and to monitor blood flow and tipping on the rim of the cup. Optic disc cupping most often results from glaucoma. Deeper in the optic disc cupping occurs due to thinning of the prelaminar and laminar layers or high intraocular pressure.